2012
DOI: 10.1093/beheco/ars168
|View full text |Cite
|
Sign up to set email alerts
|

Geometric analysis of macronutrient selection in breeds of the domestic dog, Canis lupus familiaris

Abstract: Although many herbivores and omnivores have been shown to balance their intake of macronutrients when faced with nutritionally variable foods, study of this ability has been relatively neglected in carnivores, largely on the assumption that prey are less variable in nutrient composition than the foods of herbivores and omnivores and such mechanisms therefore unnecessary. We performed diet selection studies in 5 breeds of adult dog (Canis lupus familiaris) to determine whether these domesticated carnivores regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 42 publications
5
117
3
3
Order By: Relevance
“…As shown by Hewson-Hughes et al (2013), the dietary ratio of protein:fat:carbohydrates [% of ME] preferred by dogs is 30:63:7. Moreover these authors have also demonstrated that dietary fat increases palatability and food intake in dogs.…”
Section: Dietary Intakesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Hewson-Hughes et al (2013), the dietary ratio of protein:fat:carbohydrates [% of ME] preferred by dogs is 30:63:7. Moreover these authors have also demonstrated that dietary fat increases palatability and food intake in dogs.…”
Section: Dietary Intakesmentioning
confidence: 99%
“…As an omnivore with carnivore tendency, the dog prefers high fat diets (Hewson-Hughes et al 2013). Therefore, an evaluation of the properties of different fat sources available for the pet food industry is of major interest.…”
Section: Introductionmentioning
confidence: 99%
“…Studies utilizing the Geometric Framework (GF) model suggest that animals have the ability to adjust foraging and feed intake patterns to fulfill nutritional requirements (Chambers et al, 1995;Dussutour et al, 2010;Felton et al, 2009;Hewson-Hughes et al, 2012Lee et al, 2002;Mayntz et al, 2009;Raubenheimer and Simpson, 1993;Simpson and Raubenheimer, 2012). When presented with food choices, many organisms will self-regulate feed intake in such a way as to reach intake targets for one or more nutrients Simpson and Raubenheimer, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dietary intake targets for protein have been identified across many animal taxa (Chambers et al, 1995;Felton et al, 2009;Hewson-Hughes et al, 2012Lee et al, 2002;Mayntz et al, 2009;Raubenheimer and Simpson, 2003;Solon-Biet et al, 2014;Sørensen et al, 2008). Previous studies indicate that sea urchins will adjust feed intake, presumably to satisfy nutritional requirements (Fernandez and Boudouresque, 2000;McBride et al, 1999;Taylor, 2006;Wallace, 2001 individuals adjusted intake patterns to defend this target regardless of nutrient ratios or feed concentrations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These include a single‐bowl monadic test, a two‐bowl forced choice test, and operant testing. Some researchers also utilize the traditional two bowl forced choice test and modify it in order to fit their objective and needs (Fragua, Barroeta, Manzanilla, Codony, & Villaverde, ; Hewson‐Hughes et al, ; Verbrugghe, Hesta, Gulbrandson, & Janssens, ). However, none provides an indication of why a choice is preferred.…”
Section: Introductionmentioning
confidence: 99%